Culture, Politics and Biology from a Biosemiotic Perspective - Wheeler, Wendy (Recherches sémiotiques / Semiotic Inquiry, 2019)
In this article I shall offer some considerations on the implications for political thought (broadly conceived) of the relatively new interdiscipline of biosemiotics. The semiological analysis associated with the work of Ferdinand de Saussure is a now familiar part of cultural and political analysis, but its weakness has always been, first, its narrow focus on human uses of language alone, and, second, its related inability to talk about biology. Given the extent to which human mind and behaviour are an effect of biological systems, this is a considerable omission. Joining culture and nature as part of the evolution of semiotic layers in recursive biocybernetic systems, biosemiotics insists there is an ontological and practical link between both that should be part of scientifically informed political theory and policies.